Assessment and evaluation of psychosocial distress in outpatients with cancer at a university hospital in Germany: research article - Hohmann, Laura; Merx, Kirsten; Weingärtner, Simone; Schreiber, Annette; Hetjens, Svetlana; Hofmann, Wolf-Karsten; Hofheinz, Ralf-Dieter; Gencer, Deniz (Oncology research and treatment, 2023)
Introduction: Cancer patients (pts) suffer from a significant amount of psychosocial distress related to tumor disease itself or straining treatments. Despite recommendations on how to screen for and to deal with psychosocial distress in cancer pts, data about implementation of psycho-oncological interventions (poi) in outpatient settings of cancer pts are scarce. The aim of this study was to identify outpatients with cancer in need of poi and to evaluate different assessment instruments. Methods:N = 200 outpatients with hemat-/oncological malignancies were interviewed between October 2015 and December 2017 at the University Hospital Mannheim using the Basic Documentation for Psycho-Oncology (PO-Bado) and the Hornheider Screening Instrument (HSI) - both clinician-administered assessment tools - followed by descriptive, univariate, and agreement analysis. Results:N = 61 cancer pts (31%) were identified to be in need for poi considering the results of both questionnaires. The number of identified pts in need of poi was lower when analyzing the results of the PO-Bado (n = 42, 21%) and the HSI (n = 39, 20%) separately. The degree of agreement between the results of PO-Bado and HSI was low (kappa = 0.3655). Several factors like gender, age and diagnosis were identified to have significant impact on the need for poi (p ≤ 0.05). Conclusion: Our study underlines that different screening instruments for psychosocial distress may identify disparate populations of cancer pts. The study data also revealed significant characteristics that might be associated with elevated levels of psychosocial distress and a clear indication for poi. However, further analyses on larger populations of cancer pts are needed to provide information how to transfer positive screening to poi in clinical routine.